Manual de manejo agronómico del yacón (Smallanthus sonchifolius (Poepp. & Endl.) H. Robinson). - Cabrera Pintado, Rosa María; Sánchez Jhong, Kiara Julissa; Linares Estrada, Armando (Instituto Nacional de Innovación Agraria, 2020)
18 Páginas